Post-Colonial Theory and Literature: Sources and Problems of Development (a New Identity of a Post-Colonial Subject and Author) - Shcherbak, Nina F. (Polilingvialʹnostʹ i transkulʹturnye praktiki (Online), 2019)
The main aim of the article is to consider major works related to the development of post-colonial theories as well as literary sources. The term “post” is considered together with main vectors in the development of Anglophone, Francophone post-colonial literature. In relation to the historic view of colonies existence main tendencies in the development of imperial and anti-imperial theories are considered including those of Fanon, his view of the three-level development of the identity of the colonized and psychic problems that are encountered in the process of this development. F. Fanon looks at the first level of colonial assimilation, which inevitably brings to the second phase, the phase of change and distruction which then is followed by the stage of the author’s identity restoration by means of coming back to the cultural traditions and struggle during which the subject of the colony starts his struggle against the oppressed. Main views of E. Said and his views on orientalism are discussed which aim at striking at the roots of the binary opposition the west and the east proposed by white male critics. Instead a more subtle view is suggested. The views of G. Spivak and a more feminist approach are considered as well as the works by Homi Bhabha applying a more lacanian approach to hermeneutics, the views that form a new identity pattern observed in post-colonial literature thus maintaining a completely different view of post-colonial fiction.